Identification of Bacterial Isolates from Endotracheal Aspirate of Patients in Intensive Care Unit and Their Antimicrobial Susceptibility Pattern - Khatun, Mst Nazma; Shamsuzzaman, SM; Fardows, Jannatul; Siddique, Abu Bakar; Joly, Samsoon Nahar (Journal of Enam Medical College, 2018)
Background: Nosocomial infections have been discussed as a critical issue among intubated patients leading to significant morbidity and mortality. Tracheal colonization of different bacteria may be responsible for added or superinfections and may increase the risk of mortality. Irrational use of antibiotics also increases the emergence of drug-resistant bacteria. Objectives: We aimed to investigate the bacterial isolates in the endotracheal aspirates of ICU patients and to see the pattern of antibiotic susceptibility. Materials and Methods: This cross-sectional study was based on 40 specimens of endotracheal aspirates which were collected from ICU patients of Dhaka Medical College Hospital. All the specimens were processed and cultured on MacConkey and blood agar media. The isolated organisms were identified by different biochemical tests. Results: Among the 40 specimens, 38 (95%) yielded growths of different bacteria. Of them, Acinetobacter baumanni were 13 (34%), Pseudomonas aeruginosa were 6 (16%), Klebsiella pneumoniae were 3 (8%), Klebsiella oxytoca were 3 (8%) and Staphylococcus aureus were 3 (8%). All the isolated bacteria were sensitive to colistin and most of the Acinetobacter baumanni were resistant to different antibiotics. Among the 32 isolated gram-negative bacteria, 10 (31.25%) were ESBL producers. Conclusion: Most of the bacteria showed antibiotic resistance to different common antibiotics, which is very alarming for the ICU patients. J Enam Med Col 2018; 8(2): 67-73